Relationship between the application of IFRS and the accounting information quality in Jordan - Qasim Ahmad Alawaqleh (Investment Management & Financial Innovations, 2020)
The study aimed to find out the relationship between the application of international financial reporting standards (IFRS) and the accounting information quality (AIQ) in Jordan. The research data was collected from 59 industrial companies listed on the Amman Stock Exchange (ASE) between 2010 and 2018. Panel data was used to measure an independent variable (the application of IFRS), and a questionnaire (a 5-point Likert scale) was applied to measure a dependent variable (AIQ). Multiple regression was used to test hypotheses. The study concluded that the application of IFRS in terms of earnings management and trading volume had a positive relationship with AIQ. Finally, the study recommended validating the transparency of financial reporting to improve the efficiency of the Jordanian financial market.